KOSMOLOGI DALAM TAFSIR AL-IBRIZ KARYA BISRI MUSTAFA: RELASI TUHAN, ALAM DAN MANUSIA - Mahbub Ghozali (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2020)
Cosmology in Javanese perspevtive has big implications to directing the whole concept of its action. This concept animates in every Javanese perception and action when viewing the world, including in the area of interpretation of the Qur’an. One book that consistently presents its identity as a Javanese exegesis is al-Ibri>z by Bisri Mustafa. On that basis, this study aims to find the concept of cosmology in the interpretation of al-Ibri>z. Based on this aims, this research uses descriptive analysis method with the type of literature study. This study also uses data analysis techniques using the hermeneutics method by Hans-Goerg Gadamer. This study found that the relationship between God, nature and humans in the interpretation of al-Ibri>z depicted from human actions in the real world. Humans as the center of the real world, have an obligation to maintain and use the world as possible. As a consequence of this, humans must constantly carry out worship to God and maintain relationships with other humans. The action is an attempt to maintain the balance and peace of their lives in the real world which also has implications in the afterlife.